Validity of Generalized Standard Addition Method for a Mixture of Amino Acid Analysis - M. Jasim, Azhar (Iraqi Journal of Pharmaceutical Sciences, 2017)
A Modified version of the Generlized standard addition method ( GSAM) was developed. This modified version was used for the quantitative determination of arginine (Arg) and glycine ( Gly) in arginine acetyl salicylate – glycine complex . According to this method two linear equations were solved to obtain the amounts of (Arg) and (Gly). The first equation was obtained by spectrophotometic measurement of the total absorbance of (Arg) and (Gly) colored complex with ninhydrin . The second equation was obtained by measuring the total acid consumed by total amino groups of (Arg) and ( Gly). The titration was carried out in non- aqueous media using perchloric acid in glacial acetic acid as a titrant. The developed method is accurate, precise, and free from interferences and may provide a useful approach to calibrate in the direct analysis of solid sample and it is suitable method to be used as a quality control procedure. Key words: GSAM , amino acid analysis